Epidemiology of Congenital Anomalies among the Children born in Different Hospitals under Sylhet Division in Bangladesh- a Retrospective Study - Shuma, Madhabi Lata; Halder, Shimul; Datta, Bidyut Kanti (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Congenital anomalies play a significant role in perinatal and neonatal mortality. Frequency of these congenital anomalies varies in different populations. Epidemiology is the study of frequency, distribution and determinants of disease in populations. The mission of epidemiology is to contribute to the understanding of etiology and prevention of disease and to improve the health of public through excellence in research. So, this study was conducted to find out proportion, types and immediate outcome of congenital anomalies. In this retrospective and cross-sectional study all patients admitted with congenital anomalies in different hospitals of Sylhet division in Bangladesh from October 2012 to January 2013 (04 months) were included. At first, the patients were examined for major and minor congenital anomalies and recorded properly. Diagnosis of congenital anomalies was based on ultrasonography and clinical evaluation of the fetus/newborn by experienced neonatologist. Major and minor congenital anomalies were categorized depending on their life threatening effects. Various data which were obtained was analyzed by using SPSS 13. Rates and proportions were calculated with 95% confidence interval. The proportions were compared using students T-test. Level of significance was set at P<0.05.The most frequently occurring anomalies involved the central nervous system (28.33%) of which myelomeningocele was the commonest CNS defect (9.09%). According to data, females were more susceptible to myelomeningocele than the male patients. The second frequently occurring congenital anomaly was associated with cardiovascular system (15%). Patients with urogenital anomalies (6.67%) were male, except for one who had ambiguous genitalia. Congenital anomaly associated with gastrointestinal -, respiratory -, musculoskeletal -, chromosomal - and dysmorphism were noted as 11.67%, 5%, 6.67%, 5% and 3.33%, respectively. About 11% congenital anomalies were found to be linked to other body part system. After analysis of mothers lifestyle, it was likely to conclude that more stress and efforts should be given on the role of peri-conceptional vitamin supplementation to the pregnant mother. Folic acid was found to be the primary agent for prevention of congenital defects. Dhaka Univ. J. Pharm. Sci. 14(2): 225-230, 2015 (December)